PD-1/PD-L1 immune checkpoint therapy demonstrates favorable safety profile in patients with autoimmune and cholestatic liver disease - Kocheise, Lorenz; Piseddu, Ignazio; Vonderlin, Joscha; Tjwa, Eric T.; Buescher, Gustav; Meunier, Lucy; Goeggelmann, Pia; Fianchi, Francesca; Dumortier, Jérôme Roland Jean-Pierre Bernadin; Riveiro Barciela, Mar; Gevers, Tom J.G.; Terziroli Beretta-Piccoli, Benedetta; et al. (Frontiers in immunology, 2024)
Immune checkpoint inhibitors (ICI) have revolutionized the treatment of many malignancies in recent years. However, immune−related adverse events (irAE) are a frequent concern in clinical practice. The safety profile of ICI for the treatment of malignancies in patients diagnosed with autoimmune and cholestatic liver disease (AILD) remains unclear. Due to this uncertainty, these patients were excluded from ICI clinical trials and ICI are withheld from this patient group. In this retrospective multicenter study, we assessed the safety of ICI in patients with AILD.
Gesehen am 26.03.2024